INNOVATION OF LEMBANG VOCATIONAL TRAINING CENTER TO CREATE AGRICULTURAL ENTREPRENEUR - Timotius Setiawan; Dwi Purnomo; Ernah Ernah (Departemen Sosial Ekonomi Faperta Unpad, 2018)
ABSTRACTLembang Vocational Training Center (Balai Latihan Kerja/BLK Lembang) is a government vocational training institution in charge of organizing vocational training in agriculture/agribusiness for the community, especially job seekers. The challenge faced by BLK Lembang is to create agricultural entrepreneurs expected to reduce 1.8 million unemployed in West Java (BPS, 2017). This study aims to investigate the innovations undertaken by BLK Lembang in creating agricultural entrepreneurs through agricultural vocational training. The study was conducted from November to December 2017 at BLK Lembang using qualitative descriptive method. Data were collected through secondary data, observation, in-depth interviews, and Focus Group Discussion (FGD) to several key informants. The results of this study showed that BLK Lembang has performed innovations in its vocational training system in order to create agricultural entrepreneurs that include: vision and planning, demonstration and training facilities, capacity building for instructor, training program development, training contents development, utilization of material practice, On Job Training Program, and networking. In the future, BLK Lembang will take opportunities for innovation in management and work culture, human resources, training programs, membership, facilities and partnership to improve its training system and quality in order to create more agricultural entrepreneurs. Keywords: agricultural entrepreneur, agricultural innovation system, agricultural vocational training ABSTRACTBalai Latihan Kerja (BLK) Lembang adalah lembaga pelatihan kerja pemerintah yang bertugas menyelenggarakan pelatihan kerja di bidang pertanian/ agribisnis bagi masyarakat, terutama pencari kerja. Tantangan yang dihadapi oleh BLK Lembang adalah menciptakan wirausaha pertanian yang diharapkan dapat mengurangi 1,8 juta penganggur di Jawa Barat (BPS, 2017). Penelitian ini bertujuan untuk mengetahui inovasi yang dilakukan oleh BLK Lembang dalam menciptakan wirausaha pertanian melalui pelatihan kerja bidang pertanian. Penelitian dilakukan dari November hingga Desember 2017 di BLK Lembang dengan menggunakan metode deskriptif kualitatif. Data dikumpulkan melalui data sekunder, observasi, wawancara mendalam, dan Focus Group Discussion (FGD) kepada beberapa informan kunci. Hasil penelitian ini menunjukkan bahwa BLK Lembang telah melakukan inovasi dalam sistem pelatihan kerjanya untuk menciptakan wirausaha pertanian yang meliputi: visi dan perencanaan, fasilitas peraga dan pelatihan, pengembangan kapasitas untuk instruktur, pengembangan program pelatihan, pengembangan materi pelatihan, pemanfaatan bahan latihan, Program On-Job Training dan jaringan kerja sama. Di masa mendatang, BLK Lembang akan memanfaatkan peluang-peluang untuk inovasi dalam aspek manajemen dan budaya kerja, sumber daya manusia, program pelatihan, kepesertaan, fasilitas, dan jaringan kerja sama untuk meningkatkan sistem dan kualitas pelatihan dalam rangka menciptakan lebih banyak wirausaha pertanian. Kata kunci: wirausaha pertanian, sistem inovasi pertanian, pelatihan kerja pertanian